Adopting & measuring customer service quality (SQ) in Islamic banks: A case study in Bank Islam Malaysia Berhad in Segamat, Johor / Nur Insyirah Anuwar - Anuwar, Nur Insyirah (Faculty of Business Management, 2017)
This paper is conducted to identify the relationship between service quality and customer satisfaction in the Bank Islam Malaysia Berhad (BIMB), Segamat, Johor. This study employed an improved SERQUAL model by developing a unique dimension of compliance in the context of service Islamic bank industry. This paper use CARTER instrument questionnaire. The variable include in this paper are Compliance, Assurance, Tangible, Empathy, and Responsiveness (CARTER) as independent variable and Customer Satisfaction as dependent variable. A sample size of 306 respondents is conducted in BIMB, Segamat, Johor. Although Islamic banks' principal activities are based on Islamic Law, their banking businesses are no different from other banks or financial institutions. Thus Islamic banks face competition not only from conventional banks, but from new market entrants as well (Shahril, Wan Nursofiza, & Sudin, 2004). It is for this reason that there exists a need for Islamic banks to adopt service quality program to boost up their market share and profit position (Othman & Owen, 2001). The question, which Islamic banking institution is at its best providing better services to the customers as well as providing competitive products. This study adds to the existing literature by examining the adopting and measuring customer service quality in the Islamic banking industry through a case study conducted on Bank Islam Malaysia Berhad (BIMB) in Segamat, Johor by using the supporting facts and evidence from the previous studies. So, at the end of this research we can get to know the adopting and measuring customer satisfaction by using Pearson Correlation towards the services quality on the basis six dimensions or factors in BIMB, Segamat, Johor. The findings reveal that six dimensions are positive high correlation or marked relationship and also all variable in correlation are significant at the 0.01 level.